Photoelectrocatalysis device driven by solar energy and wave energy - LIU LUOYI; WANG QI; DU JIAJIA; ZHANG YI; ZHANG XINMIAO; CONG YANQING; FAN TUO; SONG ZHAN (2015)
The invention discloses a photoelectrocatalysis device driven by solar energy and wave energy. The photoelectrocatalysis device comprises a reaction chamber internally provided with a plurality of pairs of reaction electrodes and a power supply device, wherein the reaction chamber is of a floating type connected with a buoyancy part, the power supply device comprises a storage battery connected with the electrodes, and a photovoltaic plate and wave-energy power generator mechanism for charging the storage battery. According to the photoelectrocatalysis device, the solar photovoltaic battery and the wave-energy power generator are taken as driving energy, the photoelectrocatalysis reaction is synergistically driven by the solar energy and the wave energy, and additional energy consumption is not needed; the buoyancy part is arranged, so that the entire device floats on a water surface, and drifts everywhere, and the photoelectrocatalysis device has great utilization potential on water pollution treatment.